2012
DOI: 10.1007/s00280-012-1992-x
|View full text |Cite
|
Sign up to set email alerts
|

Changing the expression vector of multidrug resistance genes is related to neoadjuvant chemotherapy response

Abstract: Our results suggest that reductions in MDR gene expression in post-NAC samples in comparison with pre-NAC are associated with tumor response to FAC and CAX as well as taxotere-based NAC, while patients displaying MDR gene upregulation had resistance to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
1
24
0
9
Order By: Relevance
“…The data of our previous study suggest that changes in expression of MDR genes during the chemotherapy process or the development of adaptive MDR, but not the mRNA levels of these genes per se, are associated with NAC efficiency. In particular, reduction in MDR gene expression in post-NAC samples in comparison with pre-NAC tumors was linked with good response to chemotherapy, whereas patients displaying MDR gene upregulation exhibited resistance to therapy15. In addition, recent data indicate that chemotherapy-induced upregulation of MDR genes can result in decreased distant metastasis-16 and disease-free17 survival.…”
Section: Discussionmentioning
confidence: 99%
“…The data of our previous study suggest that changes in expression of MDR genes during the chemotherapy process or the development of adaptive MDR, but not the mRNA levels of these genes per se, are associated with NAC efficiency. In particular, reduction in MDR gene expression in post-NAC samples in comparison with pre-NAC tumors was linked with good response to chemotherapy, whereas patients displaying MDR gene upregulation exhibited resistance to therapy15. In addition, recent data indicate that chemotherapy-induced upregulation of MDR genes can result in decreased distant metastasis-16 and disease-free17 survival.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the decrease in -transporter expression during the neoadjuvant treatment relates to drug response. In contrast, the increase in the ABC gene expression was associated with no clinical response to treatment [13].…”
Section: Multidrug Resistancementioning
confidence: 65%
“…All patients with deletions of 1 3 ABCC5 gene loci, and most patients having deletions in 1 (16p13.1), 2 (10q24), ABCG1 (21q22.3), ABCG2 (4q22.1), responded favorably to NAC. So, our study demonstrated that deletion MDR gene loci can be used as predictive marker for tumor response to NAC [13,14]. We performed the prospect study to examine whether the detection of new markers for prognosis of tumor response can be useful to choose the optimal therapy.…”
Section: Multidrug Resistancementioning
confidence: 99%
“…To date, there have been no studies reporting on changes in b3-tubulin expression during the course of chemotherapy. It has been shown that during the course of chemotherapy, expression changes may occur in some molecules, and these changes are often closely associated with drug resistance [15,16]. The goal of the present study is to explore the role of b3-tubulin expression in resistance to taxane-containing chemotherapy by examining b3-tubulin expression before and throughout the course of chemotherapy.…”
Section: Introductionmentioning
confidence: 98%